30 etudes for double bass and piano - Simandl, Franz. 1840-1912 (Music Minus One, 2005)
The etudes present a consistently challenging progression of material, full of musical interest, carefully constructed to tackle such techniques as attack; variable bow speed; mordents; finger dexterity; slurred shifts; syncopation; legato leaps; strings crossing; gruppetti; and much, much more.